Social functioning among college students diagnosed with ADHD and the mediating role of emotion regulation. Issue 4 (1st October 2016) - Ryan, Julia; Ross, Samantha; Reyes, Rebecca; Kosmerly, Stacey; Rogers, Maria
ABSTRACT: Despite the many studies that have documented the association between symptoms of ADHD and social difficulties in children and adolescents, few have examined this phenomenon in college students. In addition, the underlying factors contributing to such social difficulties are still poorly understood. We hypothesised that college students with symptoms of ADHD, namely inattention and hyperactivity/impulsivity, would continue to display social behavioural difficulties, and that emotion regulation would play a mediating role in that relationship. Ninety-nine 17–24-year-old college students filled out three questionnaires to assess Inattentive and Hyperactivity/Impulsivity Symptoms, Social Skills, and Emotion Regulation abilities. Analysis revealed that emotion regulation is a significant mediator between Inattentive Symptoms and Social Skills for female students. There was no significant correlation between ADHD symptoms and Social Skills for males. Female college students report social functioning difficulties associated with their inattentive and hyperactive symptoms, and impaired emotion regulation abilities mediate this relationship for inattentive symptoms only.